The Stairway to Antibiotic Heaven: A Scaffolded Video Series on Empiric Antibiotic Selection for Fourth-Year Medical Students - Jeffrey Larnard; Jason Zucker; Rachel Gordon (MedEdPORTAL, 2020)
Introduction Inappropriate antibiotic use and spread of resistance is a well-known problem, and medical students have indicated they want additional education on appropriate use of antimicrobials. We introduced a series of short whiteboard animation videos on empiric antibiotic selection as a supplemental resource for fourth-year medical students during a transition to residency course. Methods A total of eight whiteboard animation videos on empiric antibiotic selection were created using Camtasia. The video series started with the narrowest spectrum antibiotic discussed and progressed up an antibiotic ladder to broader spectrum antibiotics. Questions were embedded in each video. Students were offered a pretest prior to viewing the video series as well as a posttest after completing the video series. After each individual video, students were offered a postvideo survey with Likert-scaled questions evaluating student perceptions of the video. All tests and surveys were anonymous. Scores of pre- and posttests were compared with unpaired t tests. Results We received 37 pretests and 14 posttests. The average score on the pretest was 66% compared with 93% on the posttest (p <.0001; 95% CI 16.78, 37.93). Seventy-two postvideo surveys were completed across all videos. Of student responses, 100% either agreed or strongly agreed that the evaluated module was an effective way to learn the material. Discussion Our results suggested that this scaffolded, interactive video animation series on antibiotic spectrum and selection was an effective learning activity.